Technology News - No. 445 - Updated Analysis of Longwall Pillar Stability (ALPS) Computer Program Incorporates New Coal Mine Roof Rating (CMRR) (The National Institute for Occupational Safety and Health (NIOSH), 1995)
To develop a comprehensive, practical method for designing longwall gate entries that considers coal pillar size, mine roof quality, and artificial support in an easy-to-use computer program.